Application Of Finger Print Therapy On Pain Level Patient Post Laparoscopy Appendectomy Operation In Recovery Room Hospital X Jakarta Barat - Endi Tiyas; Fitriana, Fitriana (Sean Institute, 2024)
Laparoscopy appendectomy is a minimally invasive operation to remove the appendix through several small incisions, rather than one large incision. So it is necessary to provide non-pharmacological interventions to patients to reduce post-surgical pain. This case report aims to determine the effectiveness of applying finger grip relaxation to reduce pain levels in post laparoscopic appendectomy patients. The method in this case report is a case study with two respondents in laparoscopic appendectomy patients due to pain discomfort. Finger grip relaxation is carried out 3 times every 15 minutes. The instrument used is the Numeric Rating Scale (NRS). The results of this case report show that by giving finger grip relaxation intervention for 45 minutes there was a significant reduction in pain levels from scale 5 to scale 2. Finger grip relaxation is an effective non-pharmacological therapy in standard nursing care interventions to reduce the pain scale after laparoscopic appendectomy.